2005
DOI: 10.1007/s00125-005-1942-9
|View full text |Cite
|
Sign up to set email alerts
|

Human proinsulin C-peptide prevents proliferation of rat aortic smooth muscle cells cultured in high-glucose conditions

Abstract: These observations suggest that C-peptide could prevent diabetic macroangiopathy by inhibiting smooth muscle cell growth and ameliorating glucose utilisation in smooth muscle cells. C-peptide may thus be a novel agent for treating diabetic macroangiopathy in patients with type 1 and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…Some studies have demonstrated the beneficial effects of C-peptide on vessels by inhibiting smooth muscle cell proliferation and migration and antiinflammatory activity in endothelial cells (2,27,28). Other studies have revealed C-peptide deposition in the arteriosclerotic lesions of diabetic patients, chemotactic activity towards monocytes and CD4C lymphocytes and the induction of vascular smooth muscle cell proliferation (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the beneficial effects of C-peptide on vessels by inhibiting smooth muscle cell proliferation and migration and antiinflammatory activity in endothelial cells (2,27,28). Other studies have revealed C-peptide deposition in the arteriosclerotic lesions of diabetic patients, chemotactic activity towards monocytes and CD4C lymphocytes and the induction of vascular smooth muscle cell proliferation (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The few studies available on the topic have tested the effect of C-peptide on low and high glucose-induced proliferative activities of vascular smooth muscle cells, one major component involved in the formation of atherosclerotic plaque [33,34]. Here, we wanted to expand upon these studies by evaluating the potential effects of C-peptide on the endothelial cell component of the vessel wall during hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to endothelial cells, vascular smooth muscle cells also appear to be the target of beneficial effects of C-peptide on the vasculature in conditions of hyperglycaemia [33,44]. Physiological concentrations of C-peptide attenuate glucoseinduced hyperproliferation of vascular smooth muscle cells [33,44], a phenomenon associated, at least in part, with a specific inhibitory effect on NF-κB [44].…”
Section: Discussionmentioning
confidence: 99%
“…The internalisation of C-peptide was explored in human aortic endothelial cells (HAEC) and umbilical artery smooth muscle cells (UASMC), two important targets of C-peptide activity, especially in the context of vascular dysfunction leading to vascular complications in type 1 diabetes [13][14][15][16]. We found that in these cells C-peptide internalises from the cellular surface within punctate structures, most of them co-localizing with early endosomes.…”
Section: Introductionmentioning
confidence: 99%